1981
DOI: 10.1177/29.7.6167611
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fixation in immunohistochemistry: use of formaldehyde solutions at variable pH for the localization of tyrosine hydroxylase.

Abstract: Adequate fixative in immunohistochemistry requires not only a rapid and total immobilization of the antigen, but also a sufficient preservation of its immunoreactivity and maintenance of its accessibility to the immunochemical reagents for localization. Thus, the optimal fixation condition for a specific antigen necessitates a compromise between these opposing variables and can be determined by the preparation of a series of tissues with a progressively increasing degree of fixation. Unless the results of loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 494 publications
(161 citation statements)
references
References 0 publications
4
156
0
1
Order By: Relevance
“…(iii) Dopamine-3-hydroxylase and phenylethanolamine-N-methyltransferase activities from rat adrenal glands were not inhibited by this antiserum. (iv) Immunohistochemical studies indicated that it specifically stained catecholaminergic neurons (34,35). This antibody crossreacts with rat TyrOHase and, although it has been raised against a 40,000-dalton moiety, the 62;000-dalton protein characteristic of rat TyrOHase was immunoprecipitated from a PC 12 cell lysate.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Dopamine-3-hydroxylase and phenylethanolamine-N-methyltransferase activities from rat adrenal glands were not inhibited by this antiserum. (iv) Immunohistochemical studies indicated that it specifically stained catecholaminergic neurons (34,35). This antibody crossreacts with rat TyrOHase and, although it has been raised against a 40,000-dalton moiety, the 62;000-dalton protein characteristic of rat TyrOHase was immunoprecipitated from a PC 12 cell lysate.…”
Section: Discussionmentioning
confidence: 99%
“…42 Both protocols produced similar results, but the quality of both fixation and immunohistochemistry was the best with the sequential procedure at variable pH. The eyecups containing the retina in situ were oriented to allow sagital sectioning, and cut frozen at 10 mm thickness, after removal of the cornea and lens.…”
Section: Preparation Of Retinae and Brainsmentioning
confidence: 99%
“…Rats were deeply anaesthetized with sodium pentobarbital (40 mg/kg) then perfused transcardially with a brief saline wash, followed by two different aldehyde solutions in a similar manner to that described by Berod (38). The first of these contained 4% paraformaldehyde in a 0.1 M sodium acetate buffer (pH 6.5) and the other, 4% paraformaldehyde and 0.05% gluteraldehyde (PH 9.5) in a 0.1 M sodium-borate buffer.…”
Section: Perfusion Proceduresmentioning
confidence: 99%